Antibiotic stewardship in the emergency department setting: Focus on oral antibiotic selection for adults with skin and soft tissue infections - Draper, Heather M; Rybak, Michael J; LaPlante, Kerry L; Lodise, Thomas; Sakoulas, George; Burk, Muriel; Cunningham, Francesca E (American journal of health-system pharmacy, 2024)
Abstract Purpose An advisory panel of experts was convened by the ASHP Foundation as a part of its Medication-Use Evaluation Resources initiative to provide commentary on an approach to antibiotic stewardship in the treatment of skin and soft tissue infections (SSTIs), with a focus on oral antibiotics in the emergency department (ED) setting for patients who will be treated as outpatients. Considerations include a need to update existing guidelines to reflect new antibiotics and susceptibility patterns, patient-specific criteria impacting antibiotic selection, and logistics unique to the ED setting. Summary While national guidelines serve as the gold standard on which to base SSTI treatment decisions, our advisory panel stressed that institutional guidelines must be regularly updated and grounded in local antimicrobial resistance patterns, patient-specific factors, and logistical considerations. Convening a team of experts locally to establish institution-specific guidelines as part of a comprehensive antibiotic stewardship program can ensure patients receive the most appropriate oral therapy for the outpatient treatment of SSTIs in patients visiting the ED. Conclusion SSTI treatment considerations for antibiotic selection in the ED supported by current, evidence-based guidelines, including guidance on optimal oral antibiotic selection for patients discharged for outpatient treatment, are a useful tool to improve the quality and efficiency of care, enhance patient-centric outcomes and satisfaction, decrease healthcare costs, and reduce overuse of antibiotics.